Current treatment landscape for relapsed and/or refractory multiple myeloma - Dimopoulos, M.A.; Richardson, P.G.; Moreau, P.; Anderson, K.C. (Nature Reviews Clinical Oncology, 2015)
Recent developments in the treatment of multiple myeloma have led to improvements in response rates and to increased survival; however, relapse is inevitable in almost all patients. Recurrence of myeloma is typically more aggressive with each relapse, leading to the development of treatment-refractory disease, which is associated with a shorter survival. Several phase II and III trials have demonstrated the efficacy of recently approved agents in the setting of relapsed and/or refractory multiple myeloma, including immunomodulatory agents, such as lenalidomide and pomalidomide, and proteasome inhibitors, such as bortezomib and carfilzomib. Currently, however, there is no standard treatment for patients with relapsed and/or refractory disease. This Review discusses the current treatment landscape for patients with relapsed and/or refractory multiple myeloma and highlights disease-related and patient-related factors - such as pre-existing comorbidities or toxicities - that are important considerations for clinicians when selecting an appropriate treatment regimen.